An in vitro study of the antimicrobial property of duhat (Syzygium cuminii) leaves and bark decoction - Adriano, Sheryll S.
Herb-based medicines are slowly gaining acceptance from the Filipino market due to the high cost of commercially available drugs. However, their efficacy is still in question. Scientists are continuously searching for bases for herbal medication. Svziqium cuminii Linn, is one of the herbal plants used in traditional medicine.The objective of this study was to determine the antimicrobial property of Syzvgium cumunii ( duhat ) against Staphylococcus aureus UPCC 1143, Escherichia coli UPCC 1195, and Candida albicans UPCC 2168 in vitro. The decoction of duhat leaves and bark, at 40%, 80%, and 160% concentrations were tested for antimicrobial activity against the test organisms using the Agar Cup Methods. Results of the antimicrobial test were gathered by ocular observation and the diameters of zone of inhibition were measured using a ruler under reflected light. The results of the antimicrobial test showed that duhat extracts have no antimicrobial effect against Escherichia coli and Candida albicans. Only Staphylococcus aureus exhibited susceptibility to the duhat extracts. Different concentrations of duhat samples produced varying diameters of clearing zone that increased with increasing concentration.